Retinal cadherins and the retinal cadherinopathies: current concepts and future directions - Yusuf, I; Garrett, A; Maclaren, R; Charbel Issa, P (Elsevier, 2022)
Cadherins are a superfamily of calcium-dependent intercellular adhesion molecules that are widely expressed in living tissues. Within the retina and retinal pigment epithelium (RPE), cadherins contribute to tissue morphogenesis, neural circuit formation, adherens junctions of the outer blood-retinal barrier, photoreceptor disc morphogenesis, maintenance and survival. Four monogenic disorders involving genes which encode cadherins have been identified as causes of inherited retinal degeneration: the retinal cadherinopathies (CDHR1, CDH23, PCDH15, CDH3). Biallelic variants in CDHR1 result in cone-rod dystrophy, rod-cone dystrophy or late-onset macular dystrophy which may be misclassified as dry age-related macular degeneration. Biallelic variants in CDH23 and PCDH15 underlie Usher Syndrome type 1D and 1F. Hypotrichosis with juvenile macular dystrophy results from biallelic variants in CDH3, which contributes to adherens tight junctions between RPE cells. In this review, we summarise the classification of cadherins, and the role of cadherins in the physiology and morphogenesis of the inner and outer retina. Cadherins expressed in primate photoreceptors (CDHR1, CDH23 and PCDH15) have evolved complex roles in outer segment disc morphogenesis and maintenance involving intracellular heterophilic interactions which are as yet incompletely characterised. We highlight what is currently unknown about the molecular function of these cadherins, and review the pathogenesis, clinical phenotype and molecular genetics of each monogenic retinal cadherinopathy. Genes regulating the expression and post-translational modification of retinal cadherins, or those coding for as yet unidentified interacting partners, are candidates for unsolved cases of retinal degeneration. This group of disorders is potentially treatable; we summarise the likely molecular therapeutic approaches and future directions for each retinal cadherinopathy.